Judicial intervention in penal enforcement - المدرس الدکتور هێمن عبداهلل محمد; المدرس الدکتور ڕزگار عبدالکریم صالح (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Punitive treatment of those who are sentenced under penal policy has been developed by changing the purpose of punishment from deterrence, cruelty and reprisals from the delinquent trying to change reform and reintegrate him into society. It is illogical to let this later coined by the punitive management, and making the judiciary out of execution especially with giving importance by the figh and punitive judiciary to individual punishment, in addition to that, the delinquent may not have its rights because of the bad arbitrariness which is made by the penal institution. From her, the necessity of the punitive intervention is called in order to supervise the execution of punishment in a good way that ensure the good conduct of this execution in a perfect way to led to restrict him society.